(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Dental anxiety is a common psychological issue that significantly affects the adaptability and outcomes of prosthodontic treatment, especially in elderly patients undergoing complete denture procedures. Objective: This study aims to evaluate how frequently anxiety occurs in patients undergoing complete denture treatment. It also focuses on identifying the common factors that contribute to this anxiety. Understanding these factors can help in addressing patient concerns more effectively. The goal is to improve patient comfort, cooperation, and treatment outcomes. Methods: This cross-sectional study was conducted at the Prosthodontic Department of Lahore Medical and Dental College from 20 February 2025 to 20 June 2025. A total of 105 patients aged 40–75 years undergoing complete denture treatment were included through non-probability consecutive sampling. Anxiety was measured using the Modified Dental Anxiety Scale (MDAS). A structured questionnaire based on the Geriatric Oral Health Index and validated tools was used to identify anxiety triggers and contributing factors. Results: The majority of patients exhibited moderate (10–15) or high (≥16) levels of anxiety. Contributing factors included fear of dental instruments, impression-taking procedures, denture breakage, ill-fitting prostheses, and psychological conditions like gagging and breathlessness. Conclusion: Dental anxiety is prevalent among patients undergoing complete denture treatment. Identifying key anxiety-inducing factors can help in customizing counseling and treatment protocols, resulting in improved prosthodontic outcomes and enhanced patient satisfaction.